THE SOUTHERN TELLIAN SERIES AT NUMMULITES (NE ALGERIA): STRATIGRAPHY AND STRUCTURAL CONSEQUENCES - Chadi, Mohamed; Brahim, El hadj Youcef; Djeffal, Rami (European Scientific Journal, ESJ, 2013)
The synthesis of stratigraphic and structural data of Constantinois limestone massifs has allowed the refining of the southern Tellian series at nummulites stratigraphy and proposing a structural model. The most significant sites and less disturbed by tectonics, are the Taxas syncline and southern flank of Guerioun massif, exactly at the Djebel Ras Rihane. Also, at the level of Taxas syncline, and surmounting the hard ground which ended the Aptian neritic limestone, the marly levels had provided Cenomanian microfauna: Favusella washitensis, Rotalipora appenninica, R. cushmani, R. brotzeni, Hedbergella sp., and Praeglobotruncana stephani. On the southern reverse of Djebel Ras Rihane, at the level of Chaabet Ras Chiboub notch, we can observe, on the hard ground that terminates the Aptian nerititic limestones, a clayey Cenomonian over one hundred meters of thickness. The samples from these clays have provided many Hedbergella, Rotalipora brotzeni, R. cushmani, R. globotruncanoides and Praeglobotruncana gr. Stephani. The top of these clays has provided Coniacian foraminifera and revamped Cenomanian rotalipora. The study of the stratigraphic series of southern neritic massifs allowed the refining of our predecessor’s results. Also the yellow marls stratigraphically surmounting the terminal Aptian- basal Albian through a hard ground, represents the Cenomanian-Turonian. Microscopic analysis of samples from this hard ground highlights sedimentological phenomena that attest the emersion of Constantinois platform during the terminal Aptian- basal Albian. In the Constantinois limestone massifs, ‘’the southern Tellian units at nummulites ‘’ represent the normal marly cover of neritic limestones.